Analysis of the potential for biogas upgrading to syngas via catalytic reforming in the United Kingdom. (July 2021) - Baena-Moreno, Francisco M.; Sebastia-Saez, Daniel; Pastor-Pérez, Laura; Reina, Tomas Ramirez
Abstract: The UK faces unprecedented environmental challenges which require urgent action. The promotion of renewable energy sources is a promising solution to tackle these challenges. Among these, syngas production from biogas via dry reforming of methane shows great potential as a green alternative to meet global environmental goals. The purpose of this work is to estimate the potential of syngas production from biogas in the UK and its profitability. To estimate the syngas production, we present an overview of methane dry reforming to syngas. This analysis reveals that nickel/alumina catalysts are the most popular choice for the mentioned reaction. Afterwards, the potential biogas production in the UK is obtained. Both set of data are subsequently combined to estimate the potential for syngas production from biomass in the UK. A techno-economic analysis is performed to estimate the syngas price to reach profitability. This analysis reveals syngas prices ranging from 1.15 to 1.56 €/m 3 to overcome production costs, which is higher than producing syngas from traditional fossil fuels. Further analysis has also been conducted to estimate the production of different utilisation routes for said syngas including biofuel, methanol and electricity. Highlights: Economic assessment of the UK potential for syngas production. Overview of catalytic alternatives for dry reforming of methane. The analysis reveals Scotland and areas surrounding Greater London as potential production hot spots. Syngas prices from 1.14 to 1.54 €/m3 needed to reach NPV equal to zero. Production of biodiesel and methanol are promising paths for the syngas produced.